Proposal for a protocol using an infrared microbolometer camera and wavelet analysis to study foot thermoregulation. Issue 2 (15th March 2021) - Serantoni, Vincent; Jourdan, Franck; Louche, Hervé; Sultan, Ariane
ABSTRACT: Here we propose a protocol to (i) generate skin temperature (SkT) oscillations on glabrous tissues (plantar foot) in healthy subjects under controlled clinical environment conditions; (ii) measure quantitative temperature fields with an inexpensive microbolometer (MB) infrared camera in a clinical environment; and (iii) quantify the characteristics of skin temperature (SkT) oscillations through spectral analysis. We paid particular attention to the metrology of thermal measurements, with a special bench, including four homemade black body reference areas. We propose a live calibration procedure using this setup while correcting the thermal drift. After all of these correction steps, the experimental thermal resolution (NETDexp) for the temporal variation in each pixel was about 25 mK . Finally, a movement removal procedure was also applied to the thermal images to avoid foot spatial movement over the 10-min observation period. Thermoregulation was stimulated by a 6-min walking exercise test on six volunteers and was then studied using three kinds of scalar indicators evaluated before and after exercise per thermal image pixel. We demonstrated that the 6-min walk exercise increased the thermoregulation activity beneath the plantar foot sole. Moreover, unlike manually placed local thermal probes, the indicator fields proposed in this paper allow the operator to select the exact thermoregulation activation locations and analyse the spatial distribution patterns at these locations.